2016
DOI: 10.1007/s00345-016-1796-4
|View full text |Cite
|
Sign up to set email alerts
|

A prospective risk-stratified follow-up programme for radically treated renal cell carcinoma patients: evaluation after eight years of clinical use

Abstract: After 8 years of clinical use, the outcome measures of the FUP seem to be within acceptable ranges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 29 publications
0
21
0
2
Order By: Relevance
“…Blood samples were collected after written informed consent from 118 consecutive patients with newly diagnosed renal cell carcinoma during the time period of 2007–2010 (median observation time 100 months, range 4–120 months). All patients were followed according to our risk-stratified follow-up program for surgically treated renal cell carcinoma [ 72 ]. The present study included 97 randomly selected patients from this cohort.…”
Section: Methodsmentioning
confidence: 99%
“…Blood samples were collected after written informed consent from 118 consecutive patients with newly diagnosed renal cell carcinoma during the time period of 2007–2010 (median observation time 100 months, range 4–120 months). All patients were followed according to our risk-stratified follow-up program for surgically treated renal cell carcinoma [ 72 ]. The present study included 97 randomly selected patients from this cohort.…”
Section: Methodsmentioning
confidence: 99%
“…However, most of these studies did not compare the pattern of recurrence for each subtype regarding recurrence sites or whether they were diagnosed by routine follow-up imaging or symptoms. Despite the lack of well-designed prospective cohort studies, previous data suggest that early identification and treatment of RCC recurrence may improve cancer-specific survival (CSS) and overall survival in selected patients [15][16][17]. Thus, it is imperative to develop an effective risk-based surveillance strategy for the different subtypes that takes the sites of recurrences and the dynamics of their occurrence into account.…”
Section: Introductionmentioning
confidence: 99%
“…For the high-risk group with most recurrences, the competing risk analysis showed that death from other causes had a lower incidence than that in low-and intermediate-risk groups, reflecting the high risk of death from ccRCC in this group. Finally, as observed previously, most recurrences in high-risk patients developed within 2 yr after initial surgery [3,[15][16][17]19,20,23,24]. Perhaps the most intriguing observation from the RECUR analysis is that FU may not have a major impact on curing recurrent ccRCC.…”
Section: Discussionmentioning
confidence: 63%